2013
DOI: 10.2527/jas.2013-6412
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated lysine and low-protein diets: Effects on performance, carcass characteristics and nitrogen excretion in heavy growing–finishing pigs1

Abstract: Two studies were conducted to assess the effects of dietary protein and Lys reduction on growth performance, carcass quality, N excretion, and plasma N profile in growing-finishing pigs from 35 to 180 kg. The growing trial was conducted with 72 gilts and 72 barrows with 6 pens per treatment and 6 gilts or 6 barrows per pen. Four diets with the same DE and NE were compared: 1) control diet, 2) diet with protein content reduced by 3% units compared with the control diet and supplemented with Lys HCl to match the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
9
33
1
Order By: Relevance
“…However, the Lys and methionine contents of the finishing diets used in that investigation were twice those supplied in our study. Prandini et al (2013) observed similar carcass characteristics in pigs fed diets with a CP content reduced by 3 percentage points and fortified with crystalline Lys compared to control pigs. These authors also found that low-protein diets with 50% less Lys yielded lower values for CW, dressed ham weight, and BF compared to the control.…”
Section: Carcass Weight (Kg)supporting
confidence: 70%
See 1 more Smart Citation
“…However, the Lys and methionine contents of the finishing diets used in that investigation were twice those supplied in our study. Prandini et al (2013) observed similar carcass characteristics in pigs fed diets with a CP content reduced by 3 percentage points and fortified with crystalline Lys compared to control pigs. These authors also found that low-protein diets with 50% less Lys yielded lower values for CW, dressed ham weight, and BF compared to the control.…”
Section: Carcass Weight (Kg)supporting
confidence: 70%
“…Commercial feeds for heavy pigs from 90 to 165 kg BW commonly provide 150 to 130 g CP/kg and 7.0 to 6.5 g Lys/kg feed (European Commission, 2003). In previous studies investigating the effects of decreased dietary CP contents, the diets for heavy pigs were supplemented with crystalline AA to keep the concentration of indispensable AA per kilogram of feed comparable to that of conventional diets, and no change was observed in growth performance (Galassi et al, 2010;Prandini et al, 2013). Recently, Gallo et al (2014) reported that diets containing only 117 or 108 g CP/kg and 5.8 or 4.6 g total Lys/kg were adequate to support the required growth performance of PDO heavy pigs in the ranges of 90 to 130 or 130 to 165 kg BW, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In fact in a previous trial (Zanfi et al, 2014) we observed a drop of pH values of feces in diets containing coarse ES when compared to a control soy-dry corn based diet. Organic matter CATTD of the four diets (0.81 on average) were lower than those recorded in total collection trials with heavy pigs (Zanfi and Spanghero, 2012;Zanfi et al, 2014;Prandini et al, 2013), but slightly lower than those found by Galassi et al (2010) with heavy pigs fed high fiber diets (range 0.85-86). A possible explanation for the low apparent digestibility results we found could be associated to the inaccuracy measurement of AIA in feeds or feces.…”
Section: Discussioncontrasting
confidence: 60%
“…Prandini et al (2011) and Mordenti et al (2012) found that replacing soybean meal with other protein ingredients had no consequences for the quality of the carcass and fresh and seasoned Parma hams. Many experiments on heavy pigs for dry-cured ham production have investigated even sizeable reductions in dietary CP content, but with the indispensable AA content maintained at the same level as the control diets, or in any case greater than that in the current experiment (Fabro et al, 2013;Prandini et al, 2013). These studies focused mainly on growth performance and carcass traits, but less frequently on fresh ham quality.…”
Section: Ham Quality Traitsmentioning
confidence: 92%
“…Less attention has been paid to the provision of dietary protein and indispensable AA (Mordenti et al, 2003;Bosi and Russo, 2004). In most of the studies assessing the effects of reduced dietary protein contents on restricted-fed heavy pigs supplied crystalline AA to maintain the dietary concentration of indispensable AA per kilogram of feed constant, or in any case high (Galassi et al, 2010;Fabro et al, 2013;Prandini et al, 2013). Recent experiments suggest that 13.4 or 11.7 g/d dietary SID lysine would be adequate for PDO heavy pigs in the ranges of 90-130 or 130-167 kg BW, respectively, and that greater amounts of CP and SID lysine have no influence on growth performance (Gallo et al, 2014) and carcass composition and uniformity of Goland pigs.…”
Section: Growth Performance and Feed Efficiencymentioning
confidence: 99%